Influence of Library Service Quality on Perceived Librarians’ Image in Selected Private Universities in South-West, Nigeria - Idowu, Adetoun Omolola; Oso, Dr. (Mrs) Olutoyin Olukemi (International Journal on Integrated Education, 2022)
The professional identity and image of librarians give a vivid description of library profession. Due to the emergence of information technology, library users who are the major determinants of librarians’ image have diverse perceptions about librarians’ relevance which leads to professional identity crisis. However, existing studies on librarians’ image revealed how librarians’ status and personality traits can influence library users’ perception of librarians’ image. The study aimed to investigate the influence of library service quality on the perceived librarians’ image in selected private universities in South-west, Nigeria. This study adopted descriptive survey research design of the correlational type. Total population of undergraduate students in the six purposively selected universities was 31,342. Sample size of 1,491 was selected from the population. Convenience sampling technique was used to administer questionnaire to undergraduate students met physically utilising the library resources. The findings of the study were that perception of undergraduates about library service quality and satisfaction with services offered by librarians had relationship with librarians’ image. The study concluded that quality of services offered by librarians determine the perception and image that library users have about librarians. The study recommended that management of private universities should provide necessary resources needed for effective performance, in order to improve librarians’ image among the students and train librarians on how to discharge their responsibilities to the satisfaction of the undergraduates.